Hybrid passive control system for seismic response mitigation of steel frame structures / Mohammad Hossein Mehrabi - Mohammad Hossein, Mehrabi (2020)
Large vibration forces such as from seismic excitations can cause structural damage and structural collapse in the case of intense earthquakes. A large number of novel methods and of these techniques has weaknesses and strengths. Several control devices demonstrate a two-step mechanism in which the structure's stiffness is initially raised, and then the of the first vibration period down to a region where the structural response is significantly increased. The main aim of this thesis is to propose a hybrid passive control system comprises of two phases for the seismic retrofit of moment-resisting steel frames. The first phase is a viscoelastic device called Rotary Rubber Brace Damper (RRBD), consisting of five steel plates and four layers of rubber. The second phase is a cable bracing system bundled with a pre-compressed spring (PCS). The transition between these two phases consists of an increasing stiffness as the system transitions from the viscoelastic RRBD to the cable bracing PCS. In order to develop and prove the effectiveness of the hybrid passive control system, this research is divided into two parts. The first part includes the characterization of rubber compounds and analytical modeling of the RRBD concept with the aim of ABAQUS software. Then, experimental testing was conducted to determine the material properties of the rubber compounds, and, finally, the most promising rubber compounds were selected for possible inclusion in the device. The RRBD functioned at early stages of lateral displacement, indicating that the system is effective for all levels of strategies for seismic retrofitting have been developed and successfully implemented. Any dissipation energy phase is engaged upon yielding of the device. This may result in a shift vibration. The second part of this research focuses on the PCS system. Both experimental and analytical studies were conducted, and no loosening in the cable is observed, as the cables are held in tension by the spring's force; thus, the ability of the bracing system to cause impulses is eliminated. A PCS system design procedure was developed through analytical and experimental testing and then it was used for practical implementation of the proposed system. The overall behavior of the hybrid system during testing demonstrates multi-phased behavior with the capability for energy dissipation at all deformation levels and significant energy dissipation for seismic events. It shows that the proposed hybrid system creates a unique and innovative method which enhances the strengths and offsets the weaknesses of the individual systems.